Secret self-knowledge : considering sex magick as post-theistic spirituality in Eastern, Western, and African esotericism - Beyers, Jaco (University of Pretoria, 2025)
Thesis (PhD (Biblical and Religious Studies))--University of Pretoria, 2024.